Design and Development of Online Hostel Management System to Improve Application and Management Process - Wong, Pei Ling; Mahdin, Hairulnizam (Applied Information Technology And Computer Science, 2022)
UTHM Hostel Management System is developed especially for Universiti Tun Hussein Onn Malaysia (UTHM) students and the university college hostel management. This project is proposed to assist the hostel management to manage hostel activities more efficiently. The current process is more complex and inefficient, with a time-consuming complaint process, and causes inconvenience to both students and hostel management. The project is developed based on the Waterfall model. The programming languages used to develop the system are PHP, Javascript, and SQL. MySQL acts as the database for the proposed system. The system users are the hostel admin and the student. This system allows the admin to manage notices, students, student applications, room allocation, and student complaints. The student can view notices from the hostel, submit a new application, view room details, and complaint about the hostel facilities. All the details about the UTHM Hostel Management System are reviewed in this paper.